Эколого-ценотическая роль видов травяно-кустарничкового яруса в искусственных насаждениях сосны обыкновенной - Shishkin, A. M.; Kulyasova, O. A.; Шишкин, А. М.; Кулясова, О. А. (Tyumen State University Herald. Natural Resource Use and Ecology, 2017)
The article discusses the features of the distribution of species of grasses and mosses on ecological-cenotic groups depending on age cultures of the Scots pine. It was established that the plants of the ground cover of artificial pine plantations and control mixed grass birch forests belong to 6 ecological-cenotic groups: weed, meadow, forest-steppe, deciduous, forest, pine forest and taiga. It is shown that in natural birch forests the leading cenotic role belongs to deciduous forest species, while in middle-aged pine cultures coniferous and taiga species take the important part in the formation of the living ground cover, indicating that the formation of the ecological regime peculiar to coniferous forests. The proportion of meadow and forest ecological-cenotic groups species is the highest in non-closed 15-year-old pine cultures and decreases with age pine plantations. The analysis of the herb-shrub vegetation species abundance showed that by replacing the birch edificator with pine, and with increasing the pine stands age, the participation in the composition of tier cereals significantly reduces, and the cenotic role of heather species increases. В статье рассматриваются особенности распределения видов травяно-кустарничкового покрова по эколого-ценотическим группам в зависимости от возраста культур сосны обыкновенной. Установлено, что растения напочвенного покрова искусственных сосновых насаждений и контрольных березняков разнотравных принадлежат к 6 эколого-ценотическим группам: сорные, луговые, лесостепные, лиственно-лесные, боровые и таежные. Показано, что в естественных березняках ведущую ценотическую роль играют лиственно-лесные виды, а в средневозрастных культурах сосны важное участие в сложении живого напочвенного покрова принимают боровые и таежные виды, что свидетельствует о формировании экологического режима, свойственного для хвойных лесов. Доля видов луговой и лесостепной эколого-ценотических групп наиболее высока в несомкнувшихся 15-летних культурах сосны и уменьшается с возрастом сосновых насаждений. Анализ обилия видов травяно-кустарничковой растительности показал, что при смене эдификатора березы сосной и с увеличением возраста сосновых древостоев существенно снижается участие в сложении яруса злаков и возрастает ценотическая роль видов семейства вересковые.